Pelatihan cipta dan baca puisi Makassar bagi guru Bahasa Daerah Makassar di Kabupaten Takalar - Aswati Asri; Kembong Daeng; Sakinah Fitri (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Partners of the Community Partnership Program (PKM) are Makassar Regional Language Teachers who are members of the Makassar Regional Language MGMP in Takalar Regency. The problem is: (1) generally Makassar Regional Language Teachers have not been able to create or write and read poetry well, (2) Makassar Regional Language Teachers tend to be less creative in using diction in writing (copyright) and less able to read poetry. Through this PKM training, Makassar Regional Language Teachers are expected to have confidence in writing (copyright) and reading poetry, as well as being more creative in choosing words in learning to write and more expressive when reading poetry. The PKM program aims to provide poetry training and poetry reading to Makassar Regional Language Teachers who are members of the Makassar Regional Language MGMP in Takalar Regency. In general, the method used in this activity was in the form of training for Makassar Regional Language Teachers in Takalar Regency. The training activities began with the provision of poetry reading technical material. Then, continued with the practice of reading poetry. The outputs generated in PKM activities through the training of copyright and poetry reading for Makassar Regional Language Teachers in Takalar Regency, including (1) Makassar Regional Language Teachers of Takalar Regency are able to write (copy) and read poetry well; (2) Makassar Regional Language Teachers in Takalar Regency will be creative in applying several techniques of writing (copyright) and reading poetry; and (3) Makassar Regional Language Teachers of Takalar Regency will appeal to their colleagues so that there are no Makkassar Regional Language teachers who have difficulty writing and reading poetry.